Evaluation of the efficacy of antiseptic gel solution for peritoneal lavage in generalized peritonitis - Ya. P. Feleshtynsky; O. P. Demkovych; V. V. Smishchuk (Kazimierz Wielki University, 2020)
In 80-85% of cases successful management of generalized peritonitis depends on the effect of intraoperative and postoperative peritoneal cavity lavage. The aim of the study is to improve the effectiveness of peritoneal lavage with antiseptic gel solution in patients with generalized peritonitis. Materials and methods. The analysis of the comprehensive treatment was performed in 96 cases diagnosed as generalized peritonitis at the clinic of the Department of Surgery and Proctology of P.L. Shupyk National Medical Academy of Postgraduate Education from 2016 to 2020. The patients were 23 to 76 years old (the mean age was 54.3 ± 2.1). Among them there were 63 males (65.6%) and 33 females (34.4%). Depending on the method of peritoneal cavity lavage, patients were categorized into two groups. Group I or main group, including 47 (48.96%) patients, underwent peritoneal lavage with an antiseptic gel solution in compliance with the method of our invention (patent ofUkraine № 123924 for the utility model as of 12 March 2018). Group II or comparison group, including 49 (51.04%) patients, underwent peritoneal lavage with 0.02% chlorhexidine bigluconate. Results. In group I, the use of antiseptic gel solution for peritoneal lavage reduced the number of strains from 94 to 49 (p <0.01), the number of colonies - from 43.69 Lg CFU / mL to 20.08 Lg CFU / mL, Δ = 23.61 Lg CFU / mL (p <0.01), whereas in group II, the number of strains decreased from 93 to 68 (p <0.01) and the number of colonies from 42.68 Lg CFU / mL to 30.87 Lg CFU / mL, Δ = 11.81 Lg CFU / mL (p <0.01). The study found significant reduction of the number of E. Coli strains to28 in group I compared with41 in group II and the number of colonies to 3.35 Lg CFU / mL in group I compared with 5.28 Lg CFU / mL in group II. The number of leukocytes in patients of group I was lower and amounted to 7.2 ± 0.9 comparing to 10.5 ±1.2 in patients of group II (pI-II <0.05). Dynamics of procalcitonin concentration before and after peritoneal lavage: from 5.7 ± 0.4 ng / ml to 1.1 ±0.1 in group I, from 5.9 ± 0.5 ng / ml to 3.54 ± 0, 4 ng / ml in group II (pI-II <0.05). The clinical results of the complex treatment of patients with generalized peritonitis showed that in group I the complications occurred in 10.6% (5/47) of peritonitis cases, and in group II - in 26.5% (13/49) of peritonitis cases. In group I, the average length of hospital stay was 9 ± 1.4 days comparing to 14 ± 2.2 days in group II (p <0.01). Conclusions In generalized peritonitis, an antiseptic gel solution for peritoneal lavage showed higher efficacy than water-based antiseptic due to its ability to cover the entire parietal and visceral peritoneal surface as well as maximum exposure, thus reducing the number of strains of microorganisms from 94 to 49, the number of colonies from 43,69 lg CFU / ml to 20.08 lg CFU / ml, whereas the use of water-based antiseptic helped to decrease the number of strains of microorganisms from 93 to 68, the number of colonies from 42.68 lg CFU / ml to 30.87 lg CFU / ml. In the comprehensive surgical treatment of patients with generalized peritonitis,  peritoneal lavage with antiseptic gel solution helped to reduce the overall incidence of postoperative complications to 10.6% in group I comparing to 26.5% in group II, the occurrence of abdominal abscesses to 2.13% in group I comparing to 8,16% in group II, early adhesive intestinal obstruction to 2.13% in group I comparing to 8.16% in group II, postoperative wound suppuration to 6.38% in group I comparing to 10.2% in group II. Peritoneal lavage with antiseptic gel solution also decreased the average length of in-hospital stay to 9 ±1.4 ingroup I comparing to 14 ± 2.2 days in group II.